스타이렌 올리고머를 이용한 제주도 모래 해변의 환경오염을 유발하는 요인의 정성적 평가 - 권범근(Bum Gun Kwon); 고재준(Jea-Jun Ko); 박정훈(Jeong-Hun Park) (Daehan hwan'gyeong gonghag hoeji, 2021)
목적:플라스틱 오염은 해외뿐만 아니라 국내에서도 매우 중요한 환경적 이슈이다. 이 연구의 목적은 polystyrene (PS) 플라스틱에서 유래된 styrene oligomers (SOs)를 이용하여 제주도 연안 환경의 오염을 유발하는 내･외부 요인을 평가하는 것이다. 방법:상기 목적을 달성하기 위해 이 연구는 제주도 내 주요한 모래 해변을 중심으로 주변 해수와 해사 시료를 채취하여 gas chromatography/mass spectroscopy (GC/MS)로 12종 개별 SOs 화학종의 농도를 정량적으로 분석한다. 이 연구는 SOs 화학종이 갖는 물리･화학적 특성상 모래 입자 표면에 흡착되는 성질을 이용하여, 제주도 해변의 내부 또는 외부 요인에 따른 환경 오염도를 평가한다. 결과 및 토의:제주도 해변의 해사에서 SOs 평균 농도는 최저 9.80 ng/g에서 최대 13.62 ng/g으로, 해수에서 SOs 평균 농도는 비교적 일정한 0.05~0.11 µg/L로 낮았다. 채취된 시료에 따라 SOs 개별 화학종의 농도 분포가 상당한 차이가 나지만, 대체로 7종의 styrene trimers > 4종의 styrene dimers > styrene monomer 순으로 농도가 감소하였다. 제주도 해변에서 SOs 농도는 해수보다 해사에서 매우 높았다. 이 결과는 SOs 화학종이 모래 입자 표면에 흡착되어 이동성이 제한적이어서 제주도의 주요 해변이 주로 제주도 내부 요인(예, 인구 밀도, 인구 이동에 따른 여행객 수 등)에 의해 오염될 수 있음을 의미한다. 결론:이 연구는 제주도 모래 해변이 주로 내부 요인에 의해 오염되는 것으로 보인다. 모래 해변의 오염도는 곽지 해변 < 함덕 해변, 삼양 해변, 표선 해변 < 이호테우 해변, 사계 해변 < 섭지코지 해변, 김녕 해변, 협재 해변 순으로 오염도가 클 것으로 생각된다. 이 연구가 제주도 해안 환경에서 플라스틱 오염의 원인을 평가하는데 기여할 것으로 기대된다. Objectives:Plastic pollution is a very important environmental issue in Korea as well as abroad. The objective of this study is to evaluate the internal and external factors that cause pollution of the coastal environment of Jeju Island using styrene oligomers (SOs) originated from polystyrene (PS) plastic. Methods:In order to achieve the above objective, this study is conducted to quantitatively measure the concentration of 12 individual SOs chemicals, through gas chromatography/mass spectroscopy (GC/MS) analyzing seawater and beach sand samples around sandy beaches in Jeju Island. This study evaluates the degree of environmental pollution according to internal or external factors of the sandy beach by using the physicochemical characteristic that SOs species are adsorbed on the surface of sand particles. Results and Discussion:The average concentration of SOs in the beach sand of Jeju Island ranges from a minimum of 9.80 ng/g to a maximum of 13.62 ng/g, and the average concentration of SOs in seawater is relatively low with a constant 0.05 to 0.11 µg/L. Although the concentration distribution of SOs species differs considerably depending on the sample collected, the concentration of SOs decreases in the order of styrene trimers (7 isomers) > styrene dimers (4 isomers) > styrene monomer. As a result of monitoring, the concentration of SOs at the sandy beaches of Jeju Island is much higher in the beach sand than in the seawater. This result means that the major beaches of Jeju Island can be polluted mainly by internal factors (e.g. population density, number of travelers according to population movement, and so on), because SOs species are adsorbed on the surface of the sand particles and their mobility is limited. Conclusions:This study shows that the sandy beaches of Jeju Island are mainly polluted by internal factors. It is thought that the pollution degree of the sandy beaches is the highest in the order of Gwakji Beach < Samyang Beach, Hamdeok Beach, Pyoseon Beach < Ihoteho Beach, Sagye Beach < Seopjikoji Beach, Gimnyeong Beach, and Hyeopjae Beach. This study is expected to contribute to the evaluation of the causes of plastic pollution in the coastal environment of Jeju Island. KCI Citation Count: 0